CONTRIBUTION TO LEARNING HABITS AND LEARNING INTERESTS ISLAMIC EDUCATION LEARNING RESULTS FOR CLASS VII STUDENTS SMP MUHAMMADIYAH 49 MEDAN - Rusydi Ananda; Muhammad Rifai; Waladun Shaleh (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
The research aims to determine: (1) the positive and significant contribution of students 'learning habits to the learning outcomes of Islamic Religious Education, (2) the positive and significant contribution of students' interest in learning outcomes of Islamic Religious Education, and (3) positive and significant contributions. between study habits and student interest in learning outcomes of Islamic Religious Education.  The results of the research are: (1) there is a positive and significant contribution of study habits to the learning outcomes of Islamic Religious Education students of SMP Muhammadiyah 49 Medan. This means that the higher and more positive the study habits, the higher and more positive the student learning outcomes by providing an effective contribution of 9.90%, (2) there is a positive and significant contribution between interest in learning and the learning outcomes of Islamic Religious Education students of SMP Muhammadiyah 49 Medan. This means that the higher and more positive the interest in learning, the higher and more positive the learning outcomes by providing an effective contribution of 20.00%, and (3) there is a positive and significant contribution together between study habits and interest in learning with learning outcomes of Religious Education. Islamic students of SMP Muhammadiyah 49 Medan. This means that the higher and more positive the study habits and interest in learning, the higher and more positive the learning outcomes by providing an effective contribution of 30.20%.